2006
DOI: 10.1364/oe.14.009178
|View full text |Cite
|
Sign up to set email alerts
|

Calibration-based two-frequency projected fringe profilometry: a robust, accurate, and single-shot measurement for objects with large depth discontinuities

Abstract: An improved method is proposed to perform calibration-based fringe projected profilometry using a two-frequency fringe pattern for the 3D shape measurements of objects with large discontinuous height steps. A fabrication scheme for the two-frequency pattern is described as well. The proposed method offers following major advantages: (1) only one phase measurement needed for operation, (2) easiness for calibration, (3) robust performance, especially for automatic phase unwrapping, and (4) more flexible data acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Some existing spatially encoded structuredlight methods rely on binary pseudo-random dots but either have relatively low frame rate and accuracy (Saberioon and Cisar, 2016;Sarbolandi et al, 2015) or require manual digitizing of numerous points per frame (Wolf and Konrath, 2015;Zhang et al, 2008). Other existing spatial methods use grayscale patterns which cannot be projected at high frame rates (Guan et al, 2003;Lenar et al, 2013;Sagawa et al, 2012;Su and Liu, 2006). Because we found that no existing system can automatically measure dynamic shape changes at sufficiently high speeds, we developed a custom method.…”
Section: Introductionmentioning
confidence: 99%
“…Some existing spatially encoded structuredlight methods rely on binary pseudo-random dots but either have relatively low frame rate and accuracy (Saberioon and Cisar, 2016;Sarbolandi et al, 2015) or require manual digitizing of numerous points per frame (Wolf and Konrath, 2015;Zhang et al, 2008). Other existing spatial methods use grayscale patterns which cannot be projected at high frame rates (Guan et al, 2003;Lenar et al, 2013;Sagawa et al, 2012;Su and Liu, 2006). Because we found that no existing system can automatically measure dynamic shape changes at sufficiently high speeds, we developed a custom method.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we use three-frequency heterodyne [16][17][18][19][20]. The close frequencies 70, 64 and 59 are chosen.…”
Section: The Multi-frequency Methodsmentioning
confidence: 99%
“…They use multiple cameras [3,18], multi-wavelength fringe patterns [19], fringe pattern with additional information, such as colours [20], markers [7,[21][22][23][24][25][26], more frequencies [27,28], extra patterns [1,10,29,30], etc. These approaches either use additional hardware [3,18] or need to project additional fringe patterns [1,10,29,30].…”
Section: Introductionmentioning
confidence: 99%